Effect of feeding whole linseed as a source of polyunsaturated fatty acids on performance and egg characteristics of laying hens kept at high ambient temperature - Ahmad, S.; Ahsan-ul-Haq; Yousaf, M.; Kamran, Z.; Ata-ur-Rehman; Sohail, M. U.; Shahid-ur-Rahman (Facta-fundacio Arnco Ciência Tecnologia Avicolas, 2013)
The present study was conducted to evaluate the effects of feeding whole linseed on the laying performance and egg characteristics in laying hens kept at high ambient environmental temperatures (average 34 degrees C; the diurnal temperature range 26 degrees C to 41 degrees C). Two hundred and forty 38-wk-old white Leghorn laying hens were fed diets containing 0, 5, 10 or 15% whole linseed (as a source of n-3 polyunsaturated fatty acids) for a period of 12 weeks. Egg production was recorded daily, while feed intake and egg characteristics were monitored on weekly basis. The results of the study demonstrated that egg production and feed intake decreased, while feed conversion ratio (FCR) per dozen of eggs increased (p <= 0.05) with increasing dietary linseed levels. Egg weight, yolk weight, albumen height, eggshell weight, and eggshell thickness were not influenced (p > 0.05) by linseed levels in the diets offered to the laying hens. The results of the present trial suggest that feeding linseed to the laying hens in hot climates has no detrimental effects on egg characteristics, but has suppressive effects on egg production, feed intake and feed efficiency of laying hens.
Keywords: Linseed; n-3 PUFA; laying hens; hot climate; performance